Die Verlängerung einer modifizierten Strompreisbremse zurStärkung der deutschen Wirtschaft - Tom Krebs (Wirtschaftsdienst, 2023)
– This article summarises the results of a study on the Germany energy crisis and the need for an extension and modificationsof the electricity price break. The study shows that the energy crisis led to a short-run output loss comparable to the output losses as-sociated with the COVID-19 crisis in 2020 and the financial crisis in 2008/2009. In addition, real wage losses during the energy crisisare the largest losses on record. Finally, there is the risk of permanent economic damage leading to a period of economic stagnation.The extension and modification of the electricity price break until 2030 is an important policy instrument to help the Germany economyavoid economic stagnation. The argument in favour of such price controls is that the energy crisis has pushed the electricity price aboveits long-run equilibrium value.economic stagnation. The economiy argument in favor of such price controls is that the energy crisis haspushed the electricity price above its long-run equilibrium value.
Keywords: Q40; Q41; D40; D50; 330; Energieversorgung; Strompreis; Deutschland; Energieversorgung; Strompreis; Deutschland